Effect mechanism of nutrients on pathogenic bacteria at the sediment-water interface in eutrophic water - Wen, Sun; Yang, Zhang; Biao, Peng; Jing, Wang (Frontiers in Environmental Science, 2024)
This research analyzed the structure of microbial groups in the sediment–water interface (SWI) and the relationship between the gene expression levels of two typical pathogenic bacteria Escherichia coli and Enterococcus, and nutrient levels using modern biological techniques. The nutrient distribution at the SWI revealed significantly higher nutrient content in the sediment compared to the overlying water. According to Fick’s first law, the release flux indicated that PO43−-P in the upper reaches of the reservoir was deposited from the overlying water, while the release rate of NH4+-N, in addition to sedimentation, was significantly greater than that of PO43−P. The microbial community structure was primarily dominated by the genera Methyloparacoccus, Methylomonas, and Arenimonas. The abundances of E. coli and Enterococcus were higher in the surface sediment than in the overlying water. Pearson correlation analysis demonstrated that E. coli had a significant positive correlation with total nitrogen (TN) (p < 0.05) and total phosphorus (TP) (p < 0.05), whereas Enterococcus had a very significant positive correlation with TN and TP (p < 0.01).